Pelatihan penyusunan Rencana Bisnis dan Pemasaran Digital bagi siswa SMAK 2 Penabur Jakarta - Setianingsih, Rita Eka; Dema, Yosef (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
This community service activity, titled "Pelatihan Penyusunan Rencana Bisnis dan Pemasaran Digital bagi Siswa SMAK 2 PENABUR Jakarta," aimed to equip high school students with essential entrepreneurial skills and knowledge in digital marketing. Conducted on January 31, 2024, with the participation of 110 students, the program focused on understanding the components of a business plan and the strategic use of digital marketing to enhance entrepreneurial ventures. The training encompassed essential topics like developing business plans, conducting market analysis, and implementing digital marketing strategies, enriched with practical examples and case studies to connect theoretical concepts with real- world application. Students actively engaged in interactive sessions, including a Q&A segment, to ensure comprehensive understanding and application. The outcomes demonstrated increased awareness, confidence, and readiness among students to tackle entrepreneurial challenges in the digital era. This initiative underscores the significance of incorporating entrepreneurial education into high school curricula, laying the groundwork for nurturing creativity, self- reliance, and resilience in the next generation of entrepreneurs. Recommendations include expanding similar training programs, incorporating advanced modules, and establishing mentorship opportunities for sustainable impact.